THE ACTIVITY-COMPOSITION RELATIONSHIP OF OXYGEN AND HYDROGEN ISOTOPES IN AQUEOUS SALT SOLUTIONS: III. VAPOR-LIQUID WATER EQUILIBRATION OF NACL SOLUTIONS TO 350°C - Horita J.; Cole D.R.; Wesolowski D.J. (My University, 1995)
The effect of dissolved NaCl on equilibrium oxygen and hydrogen isotope fractionation factors between liquid water and water vapor was precisely determined in the temperature range from 130-350°C, using two different types of apparatus with static or dynamic sampling techniques of the vapor phase. The magnitude of the oxygen and hydrogen isotope effects of NaCl is proportional to the molality of liquid NaCl solutions at a given temperature. Dissolved NaCl lowers appreciably the hydrogen isotope fractionation factor between liquid water and water vapor over the entire temperature range. NaCl has little effect on the oxygen isotope fractionation factor at temperatures below about 200°C, with the magnitude of the salt effect gradually increasing from 200-350°C. Our results are at notable variance with those of Truesdell (1974) and Kazahaya (1986), who reported large oxygen and hydrogen isotope effects of NaCl with very complex dependencies on temperature and NaCl molality. Our high-temperature results have been regressed along with our previous results between 50 and 100°C (Horita et al., 1993a) and the low-temperature literature data to simple equations which are valid for NaCl solutions from 0 to at least 5 molal NaCl in the temperature range from 10-350°C. Our preliminary results of oxygen isotope fractionation in the system CaCO3-water +/- NaCl at 300°C and 1 kbar are consistent with those obtained from the liquid-vapor equilibration experiments, suggesting that the isotope salt effects are common to systems involving brines and any other coexisting phases or species (gases, minerals, dissolved species, etc.). The observed NaCl isotope effects at elevated temperatures should be taken into account in the interpretation of isotopic data of brine-dominated natural systems.